IO power from within? UNHCR's surrogate statehood in Kenya, Tanzania, and Uganda - Miller, S (2014)
This thesis examines the role of international organizations (IOs) at the domestic level. While International Relations (IR) offers an extensive literature on IOs, with understandings of IOs ranging from instruments of states to autonomous actors, it tends to ignore the role of IOs working at the domestic level, with an 'on-the-ground' presence of their own, and what this means for the IO's relationship with the state. The thesis develops a heuristic framework for understanding what is called IO 'domestication', which outlines a range of ways an IO can work domestically. It then focuses on one type domestication in particular: surrogate statehood, or cases where an IO substitutes for the state by providing services, executing functions of governance, and assuming authority in a given locale. The framework identifies indicators of surrogacy, the conditions for IO surrogacy, and reasons why it is sustained. It also considers the various types of relationship that can emerge from IO surrogacy between the IO and the state, ranging from states that willingly choose to abdicate responsibility to the IO, to states that partner with the IO. Empirically, the thesis examines these relationships through the case studies of the United Nations High Commissioner for Refugees (UNHCR) in Kenya, Tanzania and Uganda, which present a spectrum of UNHCR’s surrogacy over time. Ultimately, the thesis puts forth a counterintuitive claim: IOs that take on surrogate state properties actually have less influence on the states in which they are working. The analysis draws on two mechanisms to help explain this outcome: marginalisation of the state, and responsibility shifting.